2005
DOI: 10.1157/13078023
|View full text |Cite
|
Sign up to set email alerts
|

La acumulación de alteraciones genéticas y epigenéticas: un proceso causal clave entre el medio ambiente y las enfermedades de etiología compleja

Abstract: EDITORIAL La acumulación de alteraciones genéticas y epigenéticas:un proceso causal clave entre el medio ambiente y las enfermedades de etiología compleja (Accumulation of genetic and epigenetic alterations: a key causal process between the environment and diseases of complex etiology)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…34,35 It has been reported that DC-CIKs have a killing effect to renal cell carcinoma, multiple myeloma, leukemia, lung cancer and other tumor cells in vitro. 32,36,37 We produced DC-CIKs by co-culture of CIK and mature DC induced by HMGB1 and verified that DC-CIKs had a killing effect on A549 lung cancer cells. The mechanism how DCs affected the biological feature of CIKs is not very clear.…”
Section: Figurementioning
confidence: 80%
See 1 more Smart Citation
“…34,35 It has been reported that DC-CIKs have a killing effect to renal cell carcinoma, multiple myeloma, leukemia, lung cancer and other tumor cells in vitro. 32,36,37 We produced DC-CIKs by co-culture of CIK and mature DC induced by HMGB1 and verified that DC-CIKs had a killing effect on A549 lung cancer cells. The mechanism how DCs affected the biological feature of CIKs is not very clear.…”
Section: Figurementioning
confidence: 80%
“…According to the quantitative study comparing DNA adduct level in normal tissue between smoking and non-smoking lung cancer patients, the level of DNA adduct is significantly associated with smoking(r = 0.731, p < 0.001) [50].The elevated level of DNA adduct in lung tissue correlates with the increased amount of smoking, causing the increased possibility of mutation and the risk of lung cancer. So it is the direct evidence of lung cancer and smoking from molecular level [36,50].The META analysis shows that the mutation rate of P53 gene in the smoking are higher than the nonsmoking [OR = 3.50, 95% CI (2.45, 5.00), test for overall effect Z = 6.68, p < 0.0001]. It proves that smoking increases the chance of P53 mutation, leading to lower expression, thereby inducing lung cancer.…”
Section: Data Extractionmentioning
confidence: 99%
“…In the analysis by migrants and residents, the observed and expected frequencies are the same in Iquiteño emigrants, while, for residents in Lima from other provinces of the country, the test for the GSTM1 deletion deviates from the HWE; this deviation could be explained by evolutionary selection (Hao and Storey 2019), by mutations (new alleles created), migrations (by immigrants and migrants) (Llorca et al 2005), probable genotyping errors (Llorca et al 2005;Hao and Storey 2019) or to alleles not detected by the technique used (Arrunategui et al 2013). Several studies show that evolution drives an adaptive change in populations, with the environment (consumption of processed foods and environmental chemical agents) being a conditioning factor for allelic variants that can be beneficial in one territory and not in another, increasing or decreasing over the generations, producing a disruptive or deleterious mutation (causing various diseases, premature death or infertility in the individual) or a neutral mutation, which only cause slight changes in the phenotypes that will be expressed as normal variants (Porta and Crous 2005;Herrera-Paz 2013;Carrillo-Larco et al 2017); Díaz and Glaves (2020), indicate that diet is a critical determinant for cancer risk, estimating that dietary factors are responsible for around 30% of cancers in industrialized countries and 20% in developing countries, like Peru. Molina et al (2016) mention that the inhabitants of the Peruvian Amazon have stopped consuming their regional products, to introduce various processed and canned foods into their diet.…”
Section: Discussionmentioning
confidence: 99%